All the right moves! Positioning the Patient in the OR - Leonard, Regina (Operating Room Nurses Association of Canada Journal, 1992)
Patient care and safety in the OR is a joint responsibility of nurses, surgeons and anaesthetists. The perioperative nurse, however, is becoming more and more recognized as the main manager of the OR patient’s care co-ordination. Although other personnel may change from case to case, the nurse is the constant and consistent personnel member in the OR theatre. The responsibility for patient care co-ordination includes the management of patient positioning.